SAJIC 2008
DOI: 10.23962/10539/19778
|View full text |Cite
|
Sign up to set email alerts
|

MXit it up in the media: Media discourse analysis on a mobile instant messaging system

Abstract: Mobile instant messaging has the potential of providing the youth not only with a social space where they can interact and bond but also with a learning environment. MXit is the most popular mobile instant messaging application in South Africa. Due to its nascency, little academic research has been done on the application. The application has drawn considerable local media interest; however, most of the media coverage has been negative. Media discourse of the application is of academic interest, since media di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Android, iOS, Windows) and have become a platform for entertainment and work (Karapanos et al , 2016; Marino and Lo Presti, 2018; Wu and Lu, 2013). Previous generations of MIM apps that were popular in South Africa (SA) include ICQ (Leung, 2001) and Mxit (Alfreds and Van Zyl, 2015; Chigona and Chigona, 2008). MIM apps offer ease of use to customers of different ages and profiles, and Church and de Oliveira (2013) have indicated that the cost of using WhatsApp compared to a short message service (SMS) influences the frequency of use of the platforms.…”
Section: Introductionmentioning
confidence: 99%
“…Android, iOS, Windows) and have become a platform for entertainment and work (Karapanos et al , 2016; Marino and Lo Presti, 2018; Wu and Lu, 2013). Previous generations of MIM apps that were popular in South Africa (SA) include ICQ (Leung, 2001) and Mxit (Alfreds and Van Zyl, 2015; Chigona and Chigona, 2008). MIM apps offer ease of use to customers of different ages and profiles, and Church and de Oliveira (2013) have indicated that the cost of using WhatsApp compared to a short message service (SMS) influences the frequency of use of the platforms.…”
Section: Introductionmentioning
confidence: 99%